Exploring the integration of mobile learning applications among secondary level mathematics students - Biningu, B. (BUSE, 2024)
This research examines the integration of mobile learning applications (apps) in mathematics education within rural Nyanga, Zimbabwe, with the goal of improving school mathematics learning amid significant educational challenges. Employing a mixed-methods approach, the study collected qualitative data through interviews with a sample of ten mathematics teachers and twenty students from Nyanga, uncovering their perceptions, experiences and challenges associated with using applications such as GeoGebra, Kahoot!, Mathway, Photo Math, DragonBox and Desmos. Quantitative data were gathered through pre-test and post-test assessments to measure the impact of these applications on students' academic performance and conceptual understanding. Pre-test and post test scores were analysed using pared sample t-test and qualitative data was analysed thematically. The findings reveal that mobile learning applications notably enhance student engagement, deepen their conceptual understanding and boost motivation. Teachers leverage these tools for visualizing complex concepts, administering quizzes and providing step-by-step solutions. Despite these benefits, the study identifies several critical barriers, including unreliable internet connectivity, limited access to devices and frequent power outages. Additionally, teachers report a lack of structured training and technical support as significant impediments to maximizing the potential of mobile learning tools. To address these challenges, the study recommends investing in robust technological infrastructure, developing applications tailored to local needs and implementing comprehensive professional development programs for educators. This study provides valuable insights for policymakers, educators, and stakeholders, offering actionable recommendations to improve the integration of educational technology in resource-constrained settings.
Keywords: Mobile learning applications; Secondary level mathematics students